Konsep diri dengan kecenderungan kecemasan berbicara di depan umum pada mahasiswa - Dhema, Albertha Monika (Journal of Indonesian Psychological Science (JIPS), 2023)
The tendency of speaking anxiety is the condition of individuals who are uncomfortable and feel anxious so that they cannot compose messages when facing situations in public. However, the fact is that students often experience anxiety about speaking in public. One of the factors a person experiences anxiety when speaking in public is a person's self-confidence and abilities because it is closely related to a person's self-concept. The purpose of this study was to find out whether there is a relationship between self-concept and public speaking anxiety among students at Merdeka University Malang. The study population consisted of 12,104 students at Merdeka University Malang, using a purposive sampling technique with a sample of 270 students. The research instrument used a self-concept scale and a tendency scale of public speaking anxiety with a Likert scale model. Based on the results of hypothesis testing, indicates that self-concept has a significant negative relationship with the tendency of anxiety to speak in public. The higher the self-concept, the lower the tendency of public speaking anxiety among students at the Merdeka University of Malang. Conversely, the lower the self-concept, the higher the tendency of public speaking anxiety among students at the Merdeka University of Malang.KEY WORDS:  self concept; anxiety; public speaking anxiety; student ABSTRAKKecenderungan kecemasan berbicara yaitu kondisi individu yang tidak nyaman, merasa cemas sehingga tidak mampu menyusun pesan ketika menghadapi situasi di depan umum. Namun, faktanya mahasiswa masih sering mengalami kecemasan berbicara didepan umum. Salah satu faktor seseorang mengalami kecemasan saat berbicara didepan umum yaitu rasa percaya diri serta kemampuan yang dimiliki seseorang, karena berkaitan erat dengan konsep diri seseorang. Tujuan dari penelitian ini adalah untuk memaparkan hubungan konsep diri dengan kecemasan berbicara di depan umum pada mahasiswa Universitas Merdeka Malang. Populasi penelitian berjumlah 12.104 mahasiswa Universitas Merdeka Malang, menggunakan teknik purposive sampling dengan sampel berjumlah 270 mahasiswa. Instrumen peneliti menggunakan skala konsep dirii dan skala kecenderungan kecemasan berbicara di depan umum dengan model skala likert. Berdasarkan hasil uji hipotesis,  menunjukan bahwa konsep dirii memiliki hubungan signifikan negatif dengan kecenderungan kecemasan berbicara di depan umum. Artinya, semakin tinggi konsep diri, maka semakin rendah kecenderungan kecemasan berbicara di depan umum pada mahasiswa Universitas Merdeka Malang. Sebaliknya, semakin rendah konsep diri, maka semakin tinggi kecenderungan kecemasan berbicara di depan umum pada mahasiswa Universitas Merdeka Malang.KATA KUNCIkonsep diri; kecemasan; kecemasan berbicara di publik; mahasiswa Copyright ©2023. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0